PENGARUH TATA KELOLA PERUSAHAAN TERHADAP STRUKTUR MODAL PADA BADAN USAHA SEKTOR AGRIKULTUR YANG TERDAFTAR DALAM BURSAEFEKDI ASEAN PERIODE 2012-2016 - Jonathan Susanto; Deddy Marciano; Arif Herlambang (CALYPTRA, 2018)
The main objective of the firm is to maximize the shareholders’ wealth, though in order to achieve that, the directors sometimes misuse his authority to fulfill his own desires and neglecting shareholders’ interest. Good corporate governance needed to minimalize the conflict of interest in the firm. The corporate governance can determine firm’s capital structure especially when it comes to leverage. Leverage can be used as bonding mechanism to control directors, so the directors can act corresponding to the firm’s objective.This research wants to analyze the influence of corporate governance (audit committee size, board size, CEO tenure, director independence, profitability, size, growth) to capital structure (leverage). This research uses quantitative perspective in a panel data. The number of observation in this research are 305 observations, consist of 61 firms (14 firms from Indonesia, 6 firms form Thailand, 6 firms from Singapore, 35 firms from Malaysia) that enlisted for 2012-2016 period.